Kondisi sosial budaya dan ekonomi masyarakat Taman Wisata Kampung Warna-Warni Jodipan Malang - Chamidah, Nur; Hidayat, Hikmalyansyah; Amin, Saiful (Maliki Interdisciplinary Journal, 2024)
Slums around Malang’s Brantas River emerged due to population growth, triggering innovation from the "pro guys" community who worked with residents to turn the slums into tourist destinations and icons of Malang City, known as Kampung Warna-Wani Jodipan Malang. This study aims to determine people’s perceptions of these changes and analyze their impact from socio-cultural and economic aspects. The research method used in this study is qualitative descriptive, with data collection through interviews, observation, and documentation. The results showed that Jodipan’s transformation from a slum to a tourist village succeeded in changing residents’ perceptions, making it attractive to tourists, and increasing the income of the local community. The existence of tourist villages also strengthens relations between residents, increases awareness of environmental cleanliness, and encourages the spirit of mutual cooperation to advance tourist villages. This change also reflects the preservation of community culture, with the Brantas River Festival held every year. The transformation of slums into tourist villages not only creates new tourist attractions but also has a positive impact on the socio-cultural and economic aspects of the local community.